Pelatihan Pengolahan Limbah Perkebunan sebagai Pakan Tambahan Ternak di Kelompok Tani Buah Naga Palangka Raya - Elsandika, Gabriela; Agustiani, Reni; Ma’rifah, Siti; Heni, Anisa Nugraha; Jahra, Alvia; Justin, Axel Berkat; Setiawan, M. Abdur Rofiq (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to improve the understanding and skills of the Kelompok Tani Mulyo (Mulyo Farmer Group) in processing dragon fruit stem waste into an alternative poultry feed. The method employed was a community empowerment-based training approach, which included stages of observation, implementation, and evaluation. The evaluation instruments consisted of pre-test and post-test questionnaires, which were analyzed using a descriptive comparative technique to measure the improvement in partners’ knowledge and skills. The results of this program showed an increase in participants’ technical understanding of waste processing from 41.5% to 100%. Most participants who initially hesitated or lacked understanding of the processing techniques are now capable of independently producing feed. This improvement demonstrates that the training was effective in transferring knowledge and skills, providing a concrete solution for waste management and promoting product diversification through the creation of additional livestock feed.